PM.04 Cardiovascular Indices in the Early Identification of Pre-Eclampsia in Women at High-Risk For Hypertensive Disorders of Pregnancy. (26th April 2013) - Khalil, A; Mantovani, E; Bhide, A; Thilaganathan, B
Abstract : Objective: Biochemical markers such as PlGF have been proposed as point-of-care tests for the early identification of women at risk of hypertensive disorders. The aim of this study was to ascertain whether biophysical markers are similarly predictive for the subsequent development of pre-eclampsia. Methods: This was a prospective study of women presenting in the third trimester of pregnancy to the day assessment unit with non-proteinuric hypertension and suspected diagnosis of preeclampsia. Stroke volume index (SVI), cardiac index (CI), systemic vascular resistance index (SVRI), pulse wave velocity (PWV), aortic augmentation index (AIx) and uterine artery Doppler mean pulsatility index (PI) were measured at recruitment. Comparisons of medians between groups were performed using Mann Whitney tests. Results: A total of 102 women took part in the study and 42 women developed hypertensive disease in pregnancy. At presentation, compared to those who remained normotensive, women who develop hypertensive disease in pregnancy have significantly higher SVRI (3251 vs 1851 dynes – sec/cm–5/m2, P < 0.001), aortic AIx (18.0 vs 5.05%, P < 0.001), PWV (8.41 vs 7.70 m/sec, P = 0.003) and uterine artery Doppler mean PI (0.87 vs 0.77, P = 0.044). However they had significantly lower heart rate (79.8 vs 87.3 beat/min, P = 0.006), CI (2.86 vs 3.83 L/min/m2, P < 0.001) and SVI (37.5 vs 45.3 mL/m2/beat, P = 0.01). Conclusion: Women who subsequently develop pre-eclampsia have distinct cardiovascular indices that may help discriminate them from those at high-risk of pre-eclampsia who remain normotensive. It remains to be established whether these indices may be used prospectively, either alone or in conjunction with biochemical markers, for triage and follow-up.